Alterations of MicroRNA expression patterns in human cervical carcinoma cells (Ca Ski) toward 1â'S-1â'-acetoxychavicol acetate and cisplatin - Phuah, N.H.; In, L.L.A.; Azmi, M.N.; Ibrahim, H.; Awang, Khalijah; Nagoor, Noor Hasima (2013)
The aims of this study were to investigate the combined effects of a natural compound 1²S-1²-acetoxychavicol acetate (ACA) with cisplatin (CDDP) on HPV-positive human cervical carcinoma cell lines (Ca Ski - low cisplatin sensitivity and HeLa - high cisplatin sensitivity), and to identify microRNAs (miRNAs) modulated in response toward ACA and/or CDDP. It was revealed that both ACA and CDDP induced dose- and time-dependent cytotoxicity when used as a stand-alone agent, while synergistic effects were observed when used in combination with a combination index (CI) value of 0.74 Â± 0.01 and 0.85 Â± 0.01 in Ca Ski and HeLa cells, respectively. A total of 25 miRNAs were found to be significantly differentially expressed in response to ACA and/or CDDP. These include hsa-miR-138, hsa-miR-210, and hsa-miR-744 with predicted gene targets involved in signaling pathways regulating apoptosis and cell cycle progression. In conclusion, ACA acts as a chemosensitizer which synergistically potentiates the cytotoxic effect of CDDP in cervical cancer cells. The altered miRNA expression upon administration of ACA and/or CDDP suggests that miRNAs play an important role in anticancer drug responses, which can be manipulated for therapeutic purposes. Â© The Author(s) 2012.